An Analysis of a Flexible Dry Surface Electrodes - Amelia Wong Azman; Muhammad Farhan Azman; Siti Mohd Ariff; Yasir Mohd Mustafah; Huda Adibah Mohd Ramli; AHM Zahirul Alam; Mohamed Hadi Habaebi (Institute of Advanced Engineering and Science, 2018)
In the medical field, electrodes are commonly used either to retrieve signals or to conduct current. Most of the off-the-shelf surface electrodes are made from metal or rigid substrates. This paper presents a work on designing a new flexible dry electrodes using poly(3,4-ethylenedioxythiophene) polystyrene sulfonate and silver by means of dispenser printing technology. The polyester cotton fabric was selected as the substrate in this electrode designed. To analyse the new proposed composites of poly(3,4-ethylenedioxythiophene) polystyrene sulfonate and silver, different mixtures have been applied. Results from the experiment show that the conductivity of the proposed flexible electrode is comparable with the commercialized pre-gelled electrode when applied to an electrical stimulator device. Eight out of ten subjects under test described no difference in comfort between the proposed electrodes and pre-gelled electrodes.